(untitled) (Archives of Mechanics - Test, 2000)
Recently several papers were published on the subject of the CBS algorithm. This paper presents a brief summary of the theory of the algorithm and some recent findings on stabilization procedures and some appropriate boundary conditions. Several solved examples are also presented in this paper.